2023
DOI: 10.12807/ti.115201.2023.a03
|View full text |Cite
|
Sign up to set email alerts
|

The co-construction of empathic communication in interpreter-mediated medical consultations: A qualitative analysis of interaction

Abstract: Current interpreter training programs pay increasingly more attention to the intricacies of the clinical context, such as doctors and patients’ communicative goals. However, to date, the conduit model remains influential when it comes to interpreters dealing with other participants’ emotions and their own emotions in interpreter-mediated consultations (IMCs). Consequently, establishing a good doctor-patient relationship by means of empathic communication (EC) might be jeopardized in IMCs. During EC, patients e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Although the original German term has since fallen out of use, "empathy," as a concept, continues to be studied from different perspectives and in different contexts. It has been explored in clinical psychology and in clinical encounters (Riess et al, 2012), both for its importance in patient-provider interactions (see Riess et al, 2012;Boissy et al, 2016) and in interpreter-mediated scenarios (Krystallidou et al, 2018;Theys et al, 2023;Theys et al, 2022;Theys et al, 2021;Theys et al, 2020;Merlini & Gatti, 2015). There are various definitions of empathy in the literature, all of which suggest some form of feeling for another's pain and suffering (see Decety & Ickes, 2009).…”
Section: Defining Empathymentioning
confidence: 99%
See 2 more Smart Citations
“…Although the original German term has since fallen out of use, "empathy," as a concept, continues to be studied from different perspectives and in different contexts. It has been explored in clinical psychology and in clinical encounters (Riess et al, 2012), both for its importance in patient-provider interactions (see Riess et al, 2012;Boissy et al, 2016) and in interpreter-mediated scenarios (Krystallidou et al, 2018;Theys et al, 2023;Theys et al, 2022;Theys et al, 2021;Theys et al, 2020;Merlini & Gatti, 2015). There are various definitions of empathy in the literature, all of which suggest some form of feeling for another's pain and suffering (see Decety & Ickes, 2009).…”
Section: Defining Empathymentioning
confidence: 99%
“…Unlike the Krystallidou et al (2018) study, which was based on simulated interactions, several other studies were conducted on empathy in interpreter-mediated interactions (see Theys et al, 2022;Theys et al, 2021;Theys et al, 2020). The most recent by Theys et al (2023) was a qualitative study on the interpreter's impact on the verbal co-construction of empathic communication in clinical consultations. They found that the different interlocutors (patient-provider-interpreter) co-construct empathic communication, with interpreters having both control and power over said co-construction (Theys et al, 2023).…”
Section: Empathy In Interpreter-mediated Interactionsmentioning
confidence: 99%
See 1 more Smart Citation